Advances and New Trends in Environmental and Energy Informatics Selected and Extended Contributions from the 28th International Conference on Informatics for Environmental Protection - Marx Gomez, Jorge; Sonnenschein, Michael; Vogel, Ute.; Winter, Andreas; Rapp, Barbara; Giesen, Nils.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents the latest findings and ongoing research in the field of green information systems and green information and communication technology (ICT). It provides insights into a whole range of cross-cutting topics in ICT and environmental sciences as well as showcases how information and communication technologies allow environmental and energy efficiency issues to be handled effectively. The papers presented in this book are a selection of extended and improved contributions to the 28th International Conference on Informatics for Environmental Protection dedicated to ICT for energy efficiency. This book is essential and particularly worth reading for those who already gained basic knowledge and want to deepen and extend their expertise in the subjects mentioned above.
Part I: Green IT -- Part II: From Smart Grids to Smart Homes -- Part III: Smart Transportion -- Part IV: Sustainable Enterprises and Management -- Part V: Environmental Decision Support -- Part VI: Social Media for Sustainability.
Keywords: Business; Renewable energy resources; Management information systems; Computers; Renewable energy sources; Alternate energy sources; Green energy industries; Environmental management; Sustainable development; Business and Management; Business Information Systems; Information Systems and Communication Service; Environmental Management; Renewable and Green Energy; Business IT Infrastructure; Sustainable Development; Electronic books